PENGUATAN NILAI KARAKTER RELIGIUS DAN SIKAP PEDULI SOSIAL MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Lale Tanggis Nur Aulia Thrasne (Maharah: Journal of Islamic Education Teaching and Learning, 2024)
Negeri 2 Pujut, namely: (1) learning planning in strengthening religious character and students' social care attitudes, (2) the implementation of learning in strengthening these characters, and (3) the evaluation of learning carried out. This study uses a qualitative approach with a descriptive analysis method. Data collection techniques include interviews, observations, and documentation. The data was analyzed using Miles and Huberman's theory which included data reduction, data presentation, and data verification, with the validity of the data tested through triangulation. The results of the study show that PAI learning planning is carried out through the preparation of the syllabus, socialization of the syllabus, and the preparation of the Learning Implementation Plan (RPP). The implementation of learning is carried out through intracurricular and extracurricular activities that emphasize the formation of religious character and social care attitudes. Learning evaluation uses authentic assessments, criteria-based, and learning outcomes